Tolerance to spittlebugs (Aeneolamia varia) in Urochloa spp. and Megathyrsus maximus grasses: A dataset for plant damage phenotyping - Ruiz-Hurtado, Andres Felipe; Espitia-Buitrago, Paula; Hernández, Luis Miguel; Jauregui, Rosa N.; Cardoso, Juan Andres (Elsevier, 2024)
This dataset results from controlled experiments that assess the tolerance of Urochloa spp. and Megathyrsus maximus grasses to nymphal and adult spittlebug damage, particularly from Aeneolamia varia, which significantly impacts forage production in Neotropical regions. Data were collected under standardized conditions using high-throughput phenotyping methods, integrating image-capture techniques and analyses to ensure precise and consistent data acquisition. The dataset serves as a foundational resource for developing and validating computer vision models aimed at automated phenotyping, enabling accurate and high-throughput assessment of plant tolerance to spittlebug damage. Researchers can use the dataset to benchmark and compare different methodologies for plant damage assessment, fostering standardization and reproducibility in phenotyping studies.